'Regional Trade Courts' in the Shadow of the WTO Dispute Settlement System: The Paradox of Two Courts. Issue 1 (February 2020) - Ngangjoh-Hodu, Yenkong
Abstract : As of May 2018, over 650 notifications of RTAs had been received by the WTO Secretariat. Of these, 287 were in force. While the content of the WTO DSU has largely been replicated in most of the 'regional trade courts' adjudicatory bodies, emerging features of some of these RTAs are substantially out of line with the WTO DSU. While some RTAs cover aspects currently alien to the WTO, the degree of liberalisation contained within others seems remarkably deeper than under the WTO. Two distinct questions are therefore addressed in this article. The first is whether the proliferation of RTAs threatens in any way the existence of the WTO dispute settlement system, while the second concerns the extent to which this fragmented patchwork of 'regional trade courts' contributes to the development of international law. In order to tackle these issues, the article will first explore existing international rules relating to regional trade arrangements.